Еxperimental investigation of influence the plate vibration on the characteristics of boundary layer formed by near plate jet - Ищенко, С.А.; Бондарец, А.А. (Proceedings of National Aviation University, 2010)
The result of the experimental investigation on the influence of the plate’s vibration on characteristics of boundary layer which is formed by near plate jet has been presented in the article.